Higher education development in independent Ukraine (1991-2002) - Tkachenko, Uliana (Journal of Education, Health and Sport, 2019)
The article deals with the problem of higher education development in independentUkrainein the period 1991-2002. The main ways of reforming the education system are outlined. The priorities of the state policy in the development of education are revealed. Areas of international cooperation in the field of education and science are of great importance.